PERANCANGAN ULANG IDENTITAS VISUAL DI SEKOLAH ISLAM TERPADU LUQMANUL HAKIM KOTA BANDUNG - Darmawan, Ahmad Rumi; Prawira, Nanang Ganda; Rukmayadi, Yadi (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2024)
One of the first private Islamic schools in Arcamanik sub-district was the Luqmanul Hakim Integrated Islamic School (SIT). This school, established in 1996, has been the choice of parents for almost thirty years. Even the people around this school don't know much information. As many as 60.5% of residents in Arcamanik District, Bandung City, do not know the current logo and location of the school. Competitor Schools that have better visual identities have different situations. The ultimate goal of this design is to explain the visualization results of the redesign of the school's visual identity. This compounding collects qualitative data through interviews, questionnaires and literature studies. To support the findings, questionnaires and observations in the field were used to support the data. However, for data analysis, STP (Segmentation, Targeting, Positioning) strategies and other strategies are used. From the results of this design, it shows that 57.1% of the academic community at SIT Luqmanul Hakim are satisfied with the results. But a new visual identity approach still has to be made. Keywords: integrated Islamic school, school visual identity, redesign visual identity